Lichens from the area drained by the Peel and Mackenzie rivers, Yukon and Northwest Territories, Canada. I. Macrolichens - Bird, Charles D.; Thomson, John W.; Marsh, Alfred H.; Scotter, George W.; Wong, Pak Yau (Canadian Journal of Botany, 1980)
The distribution and general ecology of 249 macrolichen taxa is described for 230 000 km 2 of coniferous forest, open fens, and alpine terrain along the Mackenzie River in the District of Mackenzie, Northwest Territories, and the Peel River, a major tributary which rises in the Yukon Territory. Permafrost plays a major role in determining the plant communities that are present. Fire and man-made disturbances initiate succession. There are 45 new reports for the District of Mackenzie and 30 for the Yukon. Of the taxa, 86% are found in Europe, Asia, and North America, 9% are known from Asia and North America, whereas only 4% are restricted to North America. Pilophorus robustus is new to Canada. High mountains in the western part of the area, generally nonglaciated during the Wisconsinian, support a flora that contains many Arctic and Arctic–Alpine taxa. Amphi-Beringian species occur primarily in the north.